Effects of 2,4,6-trinitrotoluene (TNT) on phase I and phase II biotransformation enzymes in European eel Anguilla anguilla (Linnaeus, 1758) - DELLA TORRE, CAMILLA; CORSI, ILARIA; ARUKWE A; ALCARO L; AMATO E; FOCARDI, SILVANO ETTORE (Marine Environmental Research, 2008)
The aim of this study was to investigate effects of the explosive 2,4,6-trinitrotoluene (TNT) on liver drug metabolizing genes and enzymes in the European eel Anguilla anguilla as a model fish species. Eels were exposed in vivo for 6 h and 24 h to 0.5, 1 and 2.5 mg/L nominal concentrations of TNT. Expression of CYPIA, glutathione-S-transferase (pi-class; CST) and uridine-diphosphate glucuronosyltransferase (]family) (UDPGT) genes was investigated by RT-PCR, and 7-ethoxy- and 7-methoxyresorufln-0-deall :ylases (EROD, MROD), NADPH cyt c reductase (NADPH red), UDPGT and CST enzyme activities were measured by biochemical assays. An in vitro study was also performed, measuring only EROD activity. TNT exposure produced no modulation of CYPlA transcript expression while a significant inhibition of EROD enzyme activity was observed and confirmed in vitro. UDPGT transcript increased closedependently only at 6 h while the UDPGT activity tended to increase dose-dependently at 24 h. CST gene expression increased after 24 h and significant increases of CST activity were observed both at 6 and 24 h only at the highest TNT concentration. An increase of NADPH red activity was observed at 24 h. Our results seem to indicate an inhibitory effect of TNT on CYPI A-dependent catalytic activities and a possible involvement of phase 11 enzymes as well as NADPH red in TNT metabolism in eels.